P015 Receiving 1g azithromycin as part of mass drug administration (mda) for the control of trachoma is associated with reduced genital mycoplasma genitaliumprevalence. (8th June 2017) - Harrison, Mark; Harding-Esch, Emma; Marks, Michael; Pond, Marcus; Butcher, Robert; Solomon, Anthony; Tan, NgeeKeong; Nori, Achyuta; Kako, Henry; Mabey, David; Sadiq, STariq
Abstract : Introduction: Mass Drug Administration (MDA) with 1g oral azithromycin for ocular Chlamydia trachomatis (CT) infection, a key component of trachoma control, can concomitantly reduce genital CT prevalence. However, this dose is known to be sub-optimal for the treatment of genital Mycoplasma genitalium (MG) infection. Here we investigate factors associated with MG infection in pre- and post-MDA sample sets. Methods: Pre-MDA (T1) and 6 months post-MDA (T2) CT-negative self-collected vulvo-vaginal swabs from women attending three outpatient antenatal clinics (Honiara, Solomon Islands), were tested for MG infection using nucleic acid amplification. Logistic regression was used to determine factors associated with infection. Variables tested included: patient age, clinic attended, ethnicity, time spent in education, living in an urban or rural environment, marital status, living with spouse, presence of symptoms associated with a sexually transmitted infection (STI), having an STI in the last 12 months, current CT, Gonorrhoea or Trichomonas vaginalis infection, and at T2 only receipt of MDA dose. Results: MG positivity was found in 11.9% (95%CI: 8.3–16.6; 28/236) of women at T1 and in 10.9% (95%CI: 7.7–15.4; 28/256) at T2 (p=0.7467). The only factor associated with having an MG infection was history of not having received MDA with azithromycin at T2 (odds ratio 0.19, 95%CI 0.07–0.53, p=0.001). Discussion: Not having MG infection was associated with receiving 1g azithromycin as part of MDA for trachoma control six months previously. However there was no overall drop in population prevalence, indicating individual but not population benefits of MDA with regard to MG infection control.